2003
DOI: 10.1088/0953-8984/15/23/202
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic structure of liquid hydrogen

Abstract: Hydrogen makes the simplest molecular liquid. Nonetheless, due to several different reasons, measuring its microscopic structure has been one of the most challenging tasks in neutron diffraction experiments. The recent development of modern pulsed neutron sources triggered a renewed experimental interest which, in turn, led to new knowledge and also to a more effective use of the classic reactor-based experimental data. The contemporary development of quantum mechanical computer simulation techniques, and a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…2, the S(Q) measured here at the lowest density is in good agreement with previous neutron determinations obtained near the critical point, which show a maximum value of 2.17 and 2.4 for hydrogen and deuterium, respectively [1,4]. The larger intensity of the MDP of liquid deuterium was interpreted as a signature of a more extended structure and attributed to the smaller zero-point motion of the deuterium molecule with respect to that of hydrogen [22]. In contrast here, no difference in the shape of the main peak between the S(Q) of liquid H 2 and of liquid D 2 is detected within the accuracy of our measurements at similar P -T conditions.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…2, the S(Q) measured here at the lowest density is in good agreement with previous neutron determinations obtained near the critical point, which show a maximum value of 2.17 and 2.4 for hydrogen and deuterium, respectively [1,4]. The larger intensity of the MDP of liquid deuterium was interpreted as a signature of a more extended structure and attributed to the smaller zero-point motion of the deuterium molecule with respect to that of hydrogen [22]. In contrast here, no difference in the shape of the main peak between the S(Q) of liquid H 2 and of liquid D 2 is detected within the accuracy of our measurements at similar P -T conditions.…”
supporting
confidence: 91%
“…An isotopic shift is also observed with slightly larger Q m for D 2 than for H 2 under the same P -T conditions. A similar isotopic shift was already reported in previous measurements performed at low temperature near the critical point [6,22]. In dense simple liquids, it is empirically found that Q m is related to the density through the relation Q m ≈ 4.4(4πρ/3) 1/3 [23].…”
supporting
confidence: 86%
“…37 The effective values used here were DW = 0.036 83 Å and d e = 0.741 04 Å. 41 In this way one obtains results virtually indistinguishable from those provided by the application of the well-known Young-Koppel model 42 for homonuclear diatomic molecules, which, however, requires slightly heavier computational efforts. In order to extract the CoM static structure factor, S͑Q͒, the intramolecular scattering has to be subtracted from the measured single-differential cross section and the division by the intermolecular form factor has to be carried out.…”
Section: Discussionmentioning
confidence: 81%
“…Although hydrogen is the simplest of all molecular species, its nuclear quantum effects (NQEs) dominate the structure and thermodynamical properties of condensed phases, making it difficult to elucidate them [1][2][3][4][5][6][7]. The NQEs of liquid hydrogen appear as broader radial distribution functions (RDFs), large self-diffusion coefficients even at low temperatures, and anomalous temperature dependence of thermal conductivity and shear viscosity [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%